MAKKIYYAH DAN MADANIYYAH DALAM TRADISI KODIFIKASI AL-QUR’AN PADA MASA KHULAFAUR RASYIDIN - Yulia Srianti Siregar; Sawaluddin Siregar (Yayasan Baitul Hikmah al-Zain, 2026)
The study of Makkiyyah and Madaniyyah constitutes an essential component of Qur’anic studies, as it is closely related to the historical context, characteristics of revelation, and the understanding of the gradual process of Qur’anic revelation. This article aims to analyze the position of the concepts of Makkiyyah and Madaniyyah within the tradition of Qur’anic codification during the period of the Rightly Guided Caliphs. This study employs a qualitative approach using library research by examining classical and contemporary literature related to the history of Qur’anic codification, Qur’anic sciences, and the preservation of revelation in the early Islamic period. The findings indicate that the concepts of Makkiyyah and Madaniyyah function not merely as classifications based on the place and period of revelation, but also as important instruments for understanding the chronology, social context, and thematic characteristics of the Qur’anic message. During the period of the Rightly Guided Caliphs, particularly in the collection of the Qur’an under Abu Bakr and the standardization of the muṣḥaf under Uthman ibn Affan, the understanding of the arrangement, transmission, and authenticity of Qur’anic verses became an integral part of efforts to preserve the purity of the Qur’an. This study affirms that Makkiyyah and Madaniyyah possess significant historical and methodological relevance for examining the tradition of Qur’anic codification in a more comprehensive manner.